2017
DOI: 10.1001/jama.2017.1652
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Choice of Radical Prostatectomy, External Beam Radiotherapy, Brachytherapy, or Active Surveillance and Patient-Reported Quality of Life Among Men With Localized Prostate Cancer

Abstract: IMPORTANCEPatients diagnosed with localized prostate cancer have to decide among treatment strategies that may differ in their likelihood of adverse effects.OBJECTIVE To compare quality of life (QOL) after radical prostatectomy, external beam radiotherapy, and brachytherapy vs active surveillance. DESIGN, SETTING, AND PARTICIPANTSPopulation-based prospective cohort of 1141 men (57% participation among eligible men) with newly diagnosed prostate cancer were enrolled from January 2011 through June 2013 in collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
254
4
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(282 citation statements)
references
References 29 publications
18
254
4
6
Order By: Relevance
“…Every treatment option carries short- and long-term side effects that patients must be willing to accept and manage for the rest of their lives. Surgery and radiation can cause urinary, erectile, and bowel dysfunction [4,5]; yet a recent study by Daum and colleagues reported that over a third of men who had surgery or radiation were unaware of the long-term side effects [6]. And for men with low-risk disease who may not require immediate treatment, active surveillance is a monitoring option that requires regular follow-up testing, including repeat biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Every treatment option carries short- and long-term side effects that patients must be willing to accept and manage for the rest of their lives. Surgery and radiation can cause urinary, erectile, and bowel dysfunction [4,5]; yet a recent study by Daum and colleagues reported that over a third of men who had surgery or radiation were unaware of the long-term side effects [6]. And for men with low-risk disease who may not require immediate treatment, active surveillance is a monitoring option that requires regular follow-up testing, including repeat biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al published an alternative method to compare prospectively acquired patient-reported quality of life (QoL) outcomes [8]. These authors compared RP, radiotherapy, brachytherapy and active surveillance using propensity score-weighted matched cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…17 Meta-analyses, as well as recently published data comparing active surveillance, surgery, and radiation as therapeutic options for prostate cancer, indicate improved ED with external beam radiation therapy compared with surgery. 610 …”
Section: Introductionmentioning
confidence: 99%